Pengaruh Metode Bermain Peran terhadap Hasil Belajar Siswa dalam Pembelajaran PKn dI Sekolah Dasar - sarmila, nera; Reinita, Reinita; Mayarnimar, Mayarnimar (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This study aims to determine the effect of the role-playing method on the students’ civics education learning outcome in Grade V of Elementary School Number 17 Batu Gadang, Agam. This is quantitative research with a quasi-experimental type of non-equivalent control group design. Data collection was performed using total sampling technique with the number of samples amounted to 56 students. The research instrument was in the form of a multiple-choice item test. Based on the result of the t-test with the significance 5%, it was found that ttest 3.2480 > ttabel 2.00488. Thus, it is concluded that the use of role-playing method has a significant effect on the students civics education learning outcome in Grade V of  Elementary School Number 17 Batu Gadang, Agam. Keywords: PKn, Role Playing Method, Learning Outcome